Literary Specificity of Narration in the Drawing Stylistics of Bruno Schulz - Tyczynina, Alona (Konteksty, 2021)
Upon the basis of contemporary trans-narrative methodological praxis the article presents the specificity of literary narration in the Sanatorium pod Klepsydrą (The Hourglass Sanatorium) collection close to the stylistics of drawings by Bruno Schulz. A. Tichinina proves the purposefulness of the description of visual narration and features of its decoding, which logically follows from the author’s texts. Emphasis is placed on the “parity” of text and image whose meta-imaginative potential contributes to the emergence of the unique syncretic character of the artistic method applied by Bruno Schulz. The literary narration of reminiscence, created by him, is linked with oneiric narration, the mimetic one – with dietary narration, and the factual – with fictional narration, and can be considered as the construction of narrative identity. The article comments on the specificity of Schulz’s drawn story, which in the Sanatorium pod Klepsydrą collection is dynamically supported by a view from a given perspective, expressed by the symmetry, asymmetry, and dissymmetry of forms. The fact that Józef is an omniscient narrator and possesses all the indispensable narrative competences of the character pursued, as is known, by the receptive gaze of the recipient, is stressed. Consequently, the significant stylistic mode of literary works by Bruno Schulz is focused on the narrator. Emphasis is placed on the functional nature of Schulz’s intermedial elements in the graphic works and drawings, on the borderline of an inner focalisation of the literary text
Keywords: Bruno Schulz; narrative; literary narration; visual narration